Efektivitas Penggunaan Aplikasi Layanan Aspirasi dan Pengaduan Masyarakat (SIDUMAS) Dalam Menanggapi Layanan Pengaduan Masyarakat (Suatu Studi di Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Badung) - Ni Putu Sri Purnawati; Dewa Ketut Suryawan (Journal of Contemporary Public Administration, 2024)
The community aspiration and complaint service application (SIDUMAS) was developed by the Office of Communication and Information, which is used to accommodate community complaints and aspirations in a transparent manner. The SIDUMAS application is integrated with related agencies, one of which is the Public Works and Spatial Planning Office in responding to complaints in the infrastructure sector. This SIDUMAS application is already running to accommodate community complaints and aspirations. However, there are obstacles in the application, namely the performance of the admin in verifying accounts tends to be slow. This study aims to determine the effectiveness of using the SIDUMAS application in responding to public complaints at the Badung Regency Public Works and Spatial Planning Office. The research approach used descriptive qualitative. Data collection techniques used through observation, interviews and documentation. The data sources of this research are primary data and secondary data. The study units and informants of this research amounted to 5 informants consisting of government and society. The technique of determining informants in this study using purposive sampling technique. Data analysis techniques used through data condensation, data presentation, conclusion drawing and verification. Based on the results of the study, it shows that the community and the PUPR Office can understand the use of the SIDUMAS application. In responding to public complaints related to the agency's infrastructure, it can be said that it is on target, on time and achieves its goals. There are real changes from the PUPR Office and the community while using the SIDUMAS application. However, there are some people who do not know the SIDUMAS application, account verification which tends to take a long time and there is a poor screening of complaints. So it is necessary to socialize thoroughly to the community and update the application. It is necessary to check the infrastructure with a certain period of time as a form of infrastructure maintenance and consistency in responding to public complaints at the PUPR Office of Badung Regency.